2017
DOI: 10.1038/ncomms15010
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenic adipocytes promote HDL turnover and reverse cholesterol transport

Abstract: Brown and beige adipocytes combust nutrients for thermogenesis and through their metabolic activity decrease pro-atherogenic remnant lipoproteins in hyperlipidemic mice. However, whether the activation of thermogenic adipocytes affects the metabolism and anti-atherogenic properties of high-density lipoproteins (HDL) is unknown. Here, we report a reduction in atherosclerosis in response to pharmacological stimulation of thermogenesis linked to increased HDL levels in APOE*3-Leiden.CETP mice. Both cold-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 70 publications
6
128
0
Order By: Relevance
“…This browning of WAT has been linked to decreased adiposity in rodents and humans . In addition, it has been demonstrated in rodents that thermogenic stimulation promotes HDL‐cholesterol clearance in mice . Our results reveal the physiological relevance of these processes controlling whole‐body metabolism and obesity in p107 KO mice.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This browning of WAT has been linked to decreased adiposity in rodents and humans . In addition, it has been demonstrated in rodents that thermogenic stimulation promotes HDL‐cholesterol clearance in mice . Our results reveal the physiological relevance of these processes controlling whole‐body metabolism and obesity in p107 KO mice.…”
Section: Discussionsupporting
confidence: 56%
“…In this setting, the higher uptake in WAT could be caused by an enhancement of lipolysis and lipid β‐oxidation. In this regard, it has been demonstrated that BAT activity controls plasma levels of TGs by selective uptake of TRL‐derived fatty acids and the metabolic activity of thermogenesis in adipocytes is linked to high‐density lipoprotein (HDL) metabolism, which may also explain the lipid phenotype to some extent. The higher thermogenic activity in BAT and WAT is in agreement with the higher levels of protein markers of the thermogenic program in BAT, such as UCP‐1, PRDM16, and PCG1alfa; and the up‐regulation of UCP‐1 in WAT.…”
Section: Discussionmentioning
confidence: 99%
“…To resupply fuels for cold-induced energy expenditure, lipolysis is activated in WAT, and genetic blockade of adipose tissue lipolysis blocks BAT thermogenic function (Haemmerle et al, 2006; Schreiber et al, 2017), highlighting both the role of BAT lipolysis and the role of WAT as a fuel source for BAT during cold challenge. In addition to the high levels of glucose BAT takes up in response to cold (Chondronikola et al, 2014; Cooney et al, 1985; Orava et al, 2011), it also takes up lipid and cholesterol when activated (Bartelt et al, 2011, 2017; Berbée et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In both these reports, the beneficial metabolic effects were claimed to result from enlarged muscle mass following inactivation of functional Mst in LDLR −/− mice. Several recent reports have provided strong evidence suggesting that brown fat activation could reduce hypercholesterolemia and protect from atherosclerosis development [70][71][72]. Therefore, it is possible that observed beneficial effects of Mst inactivation in LDLR −/− background could be mediated at least in part via adipose browning.…”
Section: Role Of Transforming Growth Factor-β (Tgf-β) Superfamily In mentioning
confidence: 99%